The Role of Classroom Management in Enhancing Learners’ Academic Performance: Teachers’ Experiences - Nadeem Ahmed; du Plessis Pierre (Studies in Learning and Teaching, 2024)
Learners’ academic performance is one of the most imperative elements of the classroom and a core responsibility of teachers as well as schools. Thus, it is imperative to manage a classroom in a way that is conducive to teaching and learning that can promote high academic performance. Consequently, the study aimed to examine the role of classroom management in enhancing learners' academic performance. A generic qualitative research method approach was employed in the study. A purposive sampling technique was used to select a total of 18 teachers from six government secondary schools to study the phenomenon. Therefore, it was found that effective classroom management plays an important role in learners' performance. During the research, it was found that the no availability of physical resources and poor classroom management contribute to learners, performance. Based on the research findings it was identified that teacher effectiveness, teacher preparedness and teacher social and emotional proficiency, teacher-learner relationship, and learners' motivation, behavior, and discipline are the major factors that also have a strong role on learners' performance. The schools selected to conduct research are lacking resources, and teachers are not as effective and skilled as required. Due to the lack of resources and skills, teachers can't manage classrooms which can enhance learners' academic performance. It is thus mandatory to provide resources to schools and skills and training to teachers.